Out of area or out of reach? : European military support for operations in Southwest Asia - Peters, John E.; Deshong, Howard, 1967-; Rand eBooks (Santa Monica, CA : RAND, 1995)
This report examines how Europe's military force might respond to a contingency in Southwest Asia in the next five to ten years. The examination covers the state of European forces, their preparedness for operations in a remote and demanding theater of operations, and their readiness to join a "coalition of the willing" out-of-area mission to Southwest Asia. It also considers how regional actors might respond to an incursion from the West: how and with what means they might resist and what strategy they might employ. Recommendations are given for paths the Europeans could pursue to improve their ability for expeditionary operations. The report should be helpful to those interested in defense policy, Alliance planning, military strategy, and force development, especially U.S.-European cooperation for out-of-area missions.
Introduction -- European Forces in Desert Storm -- Future Military Dimensions of Southwest Asia -- European Military Cooperation -- National Capabilities -- Multinational Formations -- Conclusions.
"National Defense Research Institute."
Includes bibliographical references (p. 129-133).
Also available on the internet via WWW in PDF format.
Keywords: Armed Forces -- Logistics; Europe -- Armed Forces -- Combat sustainability; Europe -- Military policy; Europe -- Military relations -- Middle East; Middle East -- Military relations -- Europe; Electronic books